Compatibility of Sustainable Development Concept in Corporate Social Responsibility Report: Kompatibilitas Konsep Sustainable Development pada Laporan Corporate Social Responsibility - Yuliarini, Sarah; Inayati, Titik (Universitas Muhammadiyah Sidoarjo, 2022)
Intrinsic aspect that is owned by internal management on policies related to the corporation social responsibility (CSR) program leads to the results the company wants to achieve their purposes. Based on the context of intrinsic factors, this study intends to explore facts from the internal management of a company regarding the compatible concept for sustainable development (SD) as company achievements on CSR as a program that is run by the company. This research was conducted with a qualitative approach and strengthened by a triangulation process with supporting data from the company's Sustainability Report (SR). Monetary quantity parameter or economy aspect of corporate wealth (such as tangible assets be classified as internal features or extrinsic factor) have relatable impact to sustainable development (SD), with semantic analysis method revealed intrinsic factor have not it. The contribution to outcomes is to create a conceptual framework for categories associated with sustainable development through the CSR program that is required by the government for companies to implement in Indonesia. The implication of the research is found the CSR reporting supporting economic aspect, strengthen sustainable development in practices.